Living With Implantable Cardioverter Defibrillator: A phenomenological Study - Mohammad Abbasi; Reza Negarandeh; Nahid Dehghan Nayeri (Tehran University of Medical Sciences, 2014)
Background & Aim: Implantable Cardioverter Defibrillator is the most effective treatment for cardiac dysrhythmias. Having such life-saving device is the unique experience with important changes in the patient' life. Understanding of these experiences can lead to success in treatment and follow- up.This study aimed to understand the experiences of patients with Implantable Cardioverter Defibrillator .   Methods & Materials: A qualitative study using interpretative phenomenological approach was used. Thirteen participants were selected purposefully from heart clinics of Imam Khomeini hospital (Tehran). Each semi-structured interview was conducted in the period 30 to 45 minutes. Data analysis was performed using the six steps of van Manen .   Results: The main theme of 'Start Living Again' was extracted from patients with implantable defibrillator.This theme consist of 'a sense of security', 'living with angel', 'attachment to the device' and 'attempt to maintain power' .   Conclusion: The participants with an Implantable Cardioverter Defibrillator have a life again with a sense of security and peace of mind. They try to keep this life-saving device.Therefore, health care providers, especially nurses can help this patients and their families by providing appropriate self care education .